Advances in Research on Cholera and Related Diarrheas 1983
DOI: 10.1007/978-94-009-6735-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Composition of Lipopolysaccharides of Family Vibrionaceae—Absence of 2-Keto-3-Deoxyoctonate (KDO) with the Exception of Vibrio Parahaemolyticus 06 and Plesiomonas Shigelloides—

Abstract: A comparative study was carried out on the sugar composition of lipo-polysaccharides (LPS) isolated from representative strains of members of the family Vibrionaceae including all of the constituting genera, i.e., Vibrio, Aeromonas, Photobacterium, Plesiomonas, and Lucibacterium. More than 100 strains were examined. It was found that, with the exception of Vibrio parahaemolyticus 06, 2-keto-3-deoxyoctonate (KDO), known generally as a component sugar in the core region of usual gram-negative bacterial LPS, is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
1
21
2
Order By: Relevance
“…9 The absence of Kdo in LPS from the genera Vibrio and Aeromonas has been reported in the literature. [10][11][12] It was commonly believed that Kdo was absent from the LPS of all members of the Vibrionaceae family of gramnegative bacteria. The analytical determination of Kdo was established by the thiobarbiturate-based colorimetric assay known as the Weissbach reaction.…”
Section: Introductionmentioning
confidence: 99%
“…9 The absence of Kdo in LPS from the genera Vibrio and Aeromonas has been reported in the literature. [10][11][12] It was commonly believed that Kdo was absent from the LPS of all members of the Vibrionaceae family of gramnegative bacteria. The analytical determination of Kdo was established by the thiobarbiturate-based colorimetric assay known as the Weissbach reaction.…”
Section: Introductionmentioning
confidence: 99%
“…2-Keto-3-deoxyoctonate (KDO) has been regarded as a characteristic and ubiquitous sugar constituent of gram-negative bacterial lipopolysaccharides (LPS). In our previous study (9), we demonstrated that KDO is not detectable in the LPS of V. cholerae in either the O1 or the non-O1 group by the conventional periodate-thiobarbituric acid method of Weissbach and Hurwitz under conventional hydrolysis conditions (18). Instead, some kind of O-phosphorylated KDO was detected in strong-acid hydrolysates of their LPS.…”
mentioning
confidence: 96%
“…Our results indicate an increase in phagocytic ability of macrophages after in vivo treatment of mice with V. parahaemolyticus LPS. Though there are some reports on the chemical composition of V. parahaemolyticus LPS, very little information is available on its biological activities (9,10). The present studies show that in vivo treatment of mice with this LPS causes stimulation of biochemical as well as functional activities of macrophages.…”
Section: Discussionmentioning
confidence: 48%